38 Quality of discharge summaries for patients sent home from hospital for end of life care – a repeat audit. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Kumar, Anirudh; Hunter, Sophie; England, Ruth
Abstract : Background: 30% of patients leaving acute hospitals die within 12 months. When patients leave hospital, the discharge summary letter must give adequate, appropriate information to primary care providers so they can optimise ongoing care. The standard of discharge summaries is variable; evidence suggests that quality improvement projects can enhance their value. Methods: This single centre, retrospective, repeat audit carried out by F2 doctors across an acute hospital examined the quality of 58 discharge letters written between 1st August and 31st October 2017 for patients discharged home with 'fast-track' support, anticipated to be at the end of their life. Written information in discharge summaries was audited against standards from the Royal College of Physicians as well as supplementary local standards developed for use when patients are believed to be in the last weeks of their life. Results: There is still room to improve the quality of discharge summaries for patients being 'fast-tracked' home. Compared with a baseline audit in 2015, more patients were prescribed anticipatory medications on discharge and more 'sensitive discussions' were documented. However, fewer summaries contained documentation of a patient's preference for place of care and fewer had instructions to GPs regarding care at the end of life. There was no documentation about provision of patient information leaflets. Conclusions: Engaging junior doctors in a repeat audit cycle has an impact on quality of discharge summaries. Stickers to prompt content of discharge summaries have been developed and refined. Additional teaching has been provided to Foundation Year doctors. An information leaflet for patients explaining the fast-track process has been created. A further re-audit is planned in 2019 to determine the impact of these interventions.